2008
DOI: 10.2466/pms.106.1.3-20
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Novelty and Cognitive-Related Erp Components of the Infant Brain

Abstract: This study recorded visual fixation performance and event-related brain potentials (ERPs) to examine processing of novel visual information in 6- to 7-mo.-old infants as well as to test attention- or memory-related hypotheses of the functional significance of the Nc-ERP component. Separate groups of infants were presented two versions of a novelty-probe task with three types of visual stimuli: (a) a frequent face on 70% of the trials, (b) an oddball face on 15% of the trials, and (c) novel probe stimuli on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…Finally, as discussed above, Nc latency responses to familiar versus novel stimuli varied with age. In infants of 6 months or older, novel stimuli had longer Nc latencies than familiar stimuli during visual recognition (Ackles, 2008;Kopp & Lindenberger, 2011) while the opposite pattern could be observed in infants aged 4 months or younger (this study; Karrer & Monti, 1995).…”
Section: Long-term Memory In 4-month-old Infantsmentioning
confidence: 51%
See 4 more Smart Citations
“…Finally, as discussed above, Nc latency responses to familiar versus novel stimuli varied with age. In infants of 6 months or older, novel stimuli had longer Nc latencies than familiar stimuli during visual recognition (Ackles, 2008;Kopp & Lindenberger, 2011) while the opposite pattern could be observed in infants aged 4 months or younger (this study; Karrer & Monti, 1995).…”
Section: Long-term Memory In 4-month-old Infantsmentioning
confidence: 51%
“…In children aged 6 months or older, Nc latency to novel stimuli was shown to be longer than to familiar stimuli (Ackles, 2008;Kopp & Lindenberger, 2011), indicating faster processing of the familiar ones. In contrast, 4-month-old infants of the present study showed the opposite pattern, suggesting faster processing of novel stimuli.…”
Section: Long-term Memory In 4-month-old Infantsmentioning
confidence: 97%
See 3 more Smart Citations